Industrial carbon fiber / hydrotalcite heterostructure electromagnetic wave-absorbing material and preparation method thereof

By growing nanosheet-shaped hydrotalcite in situ on industrial carbon fibers and building a carbon fiber/hydrotalcite heterostructure, it solves the problems of easy corrosion and production of electromagnetic wave absorbing materials in military aircraft, and achieves efficient and lightweight electromagnetic wave absorption effect, which is suitable for The aircraft stealth function.

CN119121620APending Publication Date: 2024-12-13QINGDAO UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411242661.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the electromagnetic wave absorbing materials of military aircraft have problems such as corrosion, easy to fall off, and short service cycle. Industrial production is limited, so it is impossible to develop lightweight, broadband, and strong attenuation high-performance electromagnetic wave absorbing materials.

Method used

Heterostructured electromagnetic wave absorbing materials are constructed by industrial carbon fiber and nanosheet-shaped hydrotalcite. NiFe-LDH nanosheets are grown in situ through surface treatment and hydrothermal reaction, forming one-dimensional fiber and three-dimensional void structures to achieve dielectric-magnetic double loss Synergistically, enhance electromagnetic wave absorption performance.

Benefits of technology

The electromagnetic wave absorbing material with low load, wide bandwidth and strong loss capability has been achieved, breaking through cost and output limitations, and can meet excellent microwave absorption effect at 5wt% dosage. It is suitable for aircraft stealth function and avoids traditional wave absorbing. The coating is prone to falling off and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121620A_ABST
    Figure CN119121620A_ABST
Patent Text Reader

Abstract

The invention discloses an industrial carbon fiber / hydrotalcite (CF / NiFe-LDH) heterostructure electromagnetic wave absorbing material and a preparation method thereof, and belongs to the technical field of electromagnetic wave absorbing materials. The CF / NiFe-LDH heterostructure electromagnetic wave-absorbing material is composed of industrial carbon fibers and nanosheet-shaped LDH, the industrial CF is in a one-dimensional fiber shape, and hexagonal nanosheet-shaped NiFe-LDH evenly grows on the surfaces of the carbon fibers in an in-situ mode. The industrial CF / NiFe-LDH heterostructure electromagnetic wave-absorbing material disclosed by the invention is light in weight, low in loading capacity, wide in frequency band and high in attenuation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an industrial carbon fiber / hydrotalcite (CF / LDH) heterostructure electromagnetic wave absorbing material and a preparation method of the material, belonging to the technical field of electromagnetic wave absorbing materials. Background Art

[0002] In recent years, with the rapid development of electronic information technology, the intelligent and coordinated network information warfare capability has been continuously improved. In order to enhance the concealment and survivability of military aircraft in electromagnetic space warfare, efficient absorbing materials are urgently needed. At present, military aircraft mainly rely on absorbing coatings to achieve stealth effects, but they have disadvantages such as easy corrosion, easy shedding, and short service life. Therefore, starting from the raw materials of the aircraft itself, developing a high-performance electromagnetic wave absorbing material with light weight, broadband, and strong attenuation ability is of great significance to realize the integration of stealth functions of fighter jets. Industrial carbon fiber (CF) is known for its low density, high modulus, high strength and excellent corrosion resistance, and has been widely used in many aspects such as the fuselage and wings of military aircraft. At the same time, CF, as a carbon-based material, has the characteristics of high conductivity and strong dielectric loss, and has been widely studied in the field of electromagnetic wave absorption. However, the imbalance between the relatively high dielectric loss and low magnetic loss of single-component CF easily causes impedance mismatch, and it is difficult to achieve wide absorption and strong loss. Therefore, it is crucial to select appropriate secondary components to decorate the fiber surface and construct a rich heterogeneous interface to improve the electromagnetic wave absorption capacity.

[0003] The two-dimensional structure of nickel-iron hydrotalcite (NiFe-LDH) has great potential in the field of electromagnetic wave absorption due to its high specific surface area and rich interlayer interfaces. At the same time, the stacked LDH nanosheets can form a rich three-dimensional void structure, which not only optimizes impedance matching, but also prolongs the propagation path of electromagnetic waves. Immobilizing NiFe-LDH on the surface of other materials can not only avoid the agglomeration of hydrotalcite powder materials, but also play the synergistic effect of the two components to realize the application of functional materials. The CF / NiFe-LDH heterostructure electromagnetic wave absorbing material constructed by combining hydrotalcite with carbon fiber is more conducive to obtaining excellent electromagnetic wave absorbing ability: on the one hand, the dielectric loss CF and the magnetic loss LDH are more easily combined to achieve impedance matching, which is conducive to a large number of electromagnetic waves entering the material; on the other hand, the rich heterogeneous interfaces of the composite material will lead to charge accumulation, aggravate the unevenness of charge distribution in the interface area, and promote the occurrence of interface polarization; at the same time, the fibers and randomly stacked nanosheets on the surface form discontinuous channels and rich interfaces, inducing multiple reflections and scattering of electromagnetic waves, greatly enhancing its electromagnetic wave absorbing ability. Moreover, the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material has obvious advantages over other fiber-based composite materials in terms of light weight and thickness. Therefore, applying composite materials with excellent absorbing properties to the surface of fighter jets will be a key step for fighter jets to achieve comprehensive stealth capabilities.

[0004] Patent CN111850821B discloses a method for preparing electromagnetic wave absorbing materials from hydrotalcite-based composite nanofibers. The composite absorbing material is composed of an inner core carbon nanotube, an outer layer of carbon nanofibers, and nickel-iron hydrotalcite attached to the surface. The electromagnetic wave material of the three-dimensional conductive network structure of carbon nanofibers, carbon nanotubes and metal nanoparticles is obtained by electrostatic spinning and calcination technology. The minimum reflection loss value at a thickness of 1.4 mm is -49.5 dB, and the effective bandwidth at a matching thickness of 1.5 mm is 4.72 GHz. However, the amount of the composite material added to paraffin has reached 30wt%, the load is relatively large, and the operation process is relatively complicated. Due to its limited production, it cannot be industrialized.

[0005] Shikun Hou et al. proposed a method for preparing a PANI@CoNi-LDH@CFC nano-antenna array electromagnetic wave absorbing material in the article "A novel approach to electromagnetic wave absorbing material design: Utilizing nano-antenna arrays for efficient electromagnetic wave capture". This method constructs CoNi-LDH nanoneedles with polyaniline coating (PANI) on the surface of carbon fiber cloth (CFC). The synergistic effect of the ternary components and the unique nano-antenna structure significantly improves the composite material's ability to capture electromagnetic waves. The minimum reflection loss value at a thickness of 1.6 mm is -57.6 dB, and the maximum effective bandwidth at 1.5 mm is 3.8 GHz. However, the amount of this material added to paraffin is relatively large, reaching 35wt%, which increases its density in the composite material, making it unsuitable for applications that pursue lightweight characteristics.

[0006] Zhao Lu et al. proposed a method for preparing a CF / RGO / LDH lightweight, flexible and efficient absorbing material in the article “Heterostructure design of carbon fiber@graphene@layereddouble hydroxides synergistic microstructure for lightweight and flexible microwave absorption”. The composite material attaches RGO to the surface of cotton-derived flexible carbon fiber (CF) by electrostatic self-assembly, and then closely arranges two-dimensional sheet-like LDH on the surface of RGO / CF to construct a unique core-sheath structure. The gap-balanced impedance matching formed by the stacking of hydrotalcite is used to coordinate the dielectric loss effect of CF / RGO to achieve excellent microwave absorption. The CF / RGO / LDH absorbing material has an optimal reflection loss of -60.9dB at a frequency of 10.3GHz at a thickness of 2.5mm, and has a maximum effective bandwidth of 6.1GHz at a thickness of 2.0mm. However, the composite material uses carbonized cotton-based fibers as a carrier, and the processing process is relatively complicated, so it cannot be mass-produced.

[0007] Zihan Wang et al. proposed a method for preparing NiFe-LDH / MXene derivatives and carbon fiber interconnected fabric absorbers in the article "NiFe LDH / MXene Derivatives Interconnected with CarbonFabric for Flexible Electromagnetic Wave Absorption". This method uses electrospinning and calcination technology to connect the NiFe-LDH / MXene network structure with the carbon mesh to construct a FeNi3 / TiO2 / CF fabric composite absorber. The large flakes of MXene are used to connect adjacent carbon fibers and promote the formation of a conductive network. When the matching thickness is 2.5 mm, the absorption performance is optimal, the minimum reflection loss value is -58.0 dB, and the corresponding effective bandwidth is 7.0 GHz. However, the content of the composite material in paraffin has reached 50wt%, which is relatively high. At the same time, the carbon nanofibers prepared by electrospinning technology are limited by production and cost, and their practical application is also limited by their mechanical properties and structural characteristics.

[0008] At present, existing research mainly focuses on the fields of in-situ grown carbon nanofibers and carbonized cotton-based fibers, but due to factors such as production process, cost, and output, industrial applications cannot be achieved. There are few literature reports on industrial carbon fiber-based electromagnetic absorbing composite materials. At the same time, some carbon fiber-based composite materials can only achieve good microwave absorption effects at a large dosage and cannot be used in lightweight occasions. Therefore, the development of a heterogeneous structure electromagnetic composite absorbing material that is simple to prepare, low in cost, has excellent performance, and can be industrially produced is of great significance for the development and production of absorbing materials and the integration of aircraft stealth functions. Summary of the invention

[0009] The purpose of the present invention is to provide an industrial CF / LDH heterostructure electromagnetic absorbing material and a preparation method thereof. The electromagnetic absorbing material has a low load, a wide absorption bandwidth, a strong loss capacity, and breaks through the limitations of cost and output, and can be industrialized.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] An industrial carbon fiber / hydrotalcite heterostructure electromagnetic wave absorbing material consists of industrial carbon fiber and nano-flaky hydrotalcite. The industrial carbon fiber is one-dimensional fiber-shaped, and hexagonal nano-flaky hydrotalcite is in-situ grown on the surface of the industrial carbon fiber.

[0012] A method for preparing the above industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material, the method comprising the following steps:

[0013] Step 1: Prepare pretreated CF: Soak the tow carbon fiber in acetone, concentrated nitric acid, and silane coupling agent / ethanol mixed solution in turn for surface treatment. After each surface treatment, wash and dry it before the next surface treatment, and finally obtain pretreated carbon fiber; the purpose of using acetone is to remove the glue from the tow carbon fiber to remove the resin and other impurities on the fiber surface, to ensure that the fiber surface is smoother and conducive to the adhesion of hydrotalcite. When concentrated nitric acid is used for surface oxidation, grooves will appear on the surface of the carbon fiber, increasing the surface area and surface roughness of the fiber, and concentrated nitric acid acidification will promote the functionalization of carboxyl / hydroxyl groups on the surface of the carbon fiber, making it easier for the positively charged hydrotalcite of the laminate to grow in situ on the surface of the carbon fiber. After modification with silane coupling agent, the surface tension of the carbon fiber can be increased, which is conducive to the uniform development of hydrotalcite on the fiber surface.

[0014] Step 2: Prepare a heterostructure composite material: dissolve metal salt 1 and metal salt 2 in deionized water, immerse the pretreated carbon fiber obtained in step 1 in the above salt solution, and after uniform dispersion, use an alkaline solution to adjust the pH value of the above mixed solution, and then transfer the precipitate to a polytetrafluoroethylene reaction container for hydrothermal reaction. After sufficient reaction, the reactant obtained is washed and dried to obtain an industrial CF / LDH heterostructure electromagnetic absorbing material.

[0015] Furthermore, in step 1, the mass volume ratio of the tow carbon fiber, acetone, concentrated nitric acid, and silane coupling agent / ethanol is 0.1-30 g: 0.1-100 mL: 0.1-100 mL: 0.1-200 g, preferably 1-20 g: 10-90 mL: 10-80 mL: 1-150 g.

[0016] Further, in step 1, the temperatures and corresponding times of the acetone, concentrated nitric acid, and silane coupling agent / ethanol treatments are 8-12h / 40-60°C, 1-5h / 50-70°C, 1-5h / 60-80°C, preferably 10h / 50°C, 3h / 60°C, 3h / 70°C, wherein the mass fraction of the silane coupling agent / ethanol is 1wt%-10wt%, and the silane coupling agents include KH450, KH550, KH560, and KH570.

[0017] Furthermore, in step 1, the drying temperature of the carbon fiber at each stage is 60 to 80° C., and the drying time is 1 to 48 hours.

[0018] Furthermore, in step 2, the molar ratio of the metal salt 1 to the metal salt 2 is 1 to 4:1.

[0019] Furthermore, in step 2, the metal salt 1 is one of nickel salt, magnesium salt, cobalt salt, zinc salt, calcium salt or copper salt; the metal salt 2 is one of iron salt, aluminum salt, chromium salt or manganese salt.

[0020] In step 2, the nickel salt is nickel nitrate hexahydrate, with a mass of 2.2257-6.677 g, the iron salt is iron nitrate nonahydrate, with a mass of 0.773-2.3191 g, and the volume of deionized water is 20-60 mL. The nickel salt and the iron salt can be selected within the above range, but the molar ratio must be 4:1. Generally, metals with a radius similar to that of magnesium ions can form other hydrotalcites. Common hydrotalcites and their ionic radii are shown in Table 1:

[0021] Table 1 Radius of metal cations

[0022]

[0023] Furthermore, in step 2, the mass ratio of the carbon fiber to the hydrotalcite is 1:1-30.

[0024] Furthermore, in step 2, the alkaline solution is one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, ammonia water, and sodium bicarbonate solution. The mass of the alkaline substance is 1.5308-4.5923 g, and the volume of deionized water is 15-40 mL.

[0025] Furthermore, in step 2, the pH of the CF / LDH precipitate is 9 to 14, the reaction temperature is 50 to 220° C., preferably 80 to 200° C., more preferably 120 to 150° C., and the reaction time is 1 to 20 h.

[0026] The beneficial effects of the present invention compared to the prior art are:

[0027] (1) The industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material of the present invention has excellent impedance matching performance and unique microstructure. The staggered overlapping carbon fibers and randomly stacked hydrotalcite nanosheets form discontinuous holes, which provide more transmission paths for multiple scattering and reflection of electromagnetic waves, and synergistically use the dielectric-magnetic dual loss mechanism to enable it to have excellent electromagnetic wave absorption performance.

[0028] (2) The real part of the dielectric constant of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material of the present invention is maintained at 5.3 to 11.9, the imaginary part of the dielectric constant is maintained at 1.9 to 3.8, and the real part of the magnetic permeability is maintained at 1.0 to 1.6, and it has excellent impedance matching and good dielectric loss capability; the prepared absorber has a minimum reflection loss of -57.77 dB at a single matching thickness and an effective bandwidth of 7.02 GHz.

[0029] (3) The industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material of the present invention is based on aircraft raw materials. It can meet excellent microwave absorption effects at a doping amount of 5wt%. It gives the aircraft an integrated stealth function while ensuring the basic use function of the aircraft, breaking through the disadvantages of easy detachment, easy corrosion and short service life of the aircraft electromagnetic absorbing coating, and realizing the diversification of the application of electromagnetic absorbing materials.

[0030] (4) The present invention uses industrial CF as a carrier and in situ grows NiFe-LDH nanosheets on the surface by a one-step hydrothermal method. The preparation process is simple and the cost is low. It successfully overcomes the production and cost constraints faced by current carbon nanofibers and carbonized cotton-based fibers, and can realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The XRD spectrum of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 of the present invention;

[0032] Figure 2A 6 μm SEM photograph of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 of the present invention;

[0033] Figure 3 A 4 μm SEM photograph of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 of the present invention;

[0034] Figure 4 This is an electromagnetic parameter diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 of the present invention;

[0035] Figure 5 This is a reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 of the present invention;

[0036] Figure 6 This is a reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 2 of the present invention;

[0037] Figure 7 This is a reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 3 of the present invention;

[0038] Figure 8 This is a reflection loss diagram of the industrial CF / NiCo-LDH heterostructure electromagnetic absorbing material prepared in Example 4 of the present invention;

[0039] Fig. 9 This is a reflection loss diagram of the industrial CF / ZnFe-LDH heterostructure electromagnetic absorbing material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0040] The technical scheme in the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work belong to the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0041] Example 1

[0042] A method for preparing an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material specifically comprises the following steps:

[0043] Step 1: Immerse 0.5g of tow carbon fiber (CF) in 50mL of acetone, remove glue at 50℃ for 10h, then rinse with deionized water several times, and dry at 70℃ for 24h. Then put the degummed carbon fiber into 50mL of concentrated nitric acid (HNO3), oxidize it at 60℃ for 3h, then rinse with deionized water until neutral, and dry it. Finally, immerse the acidified carbon fiber in 100g of KH550 solution with ethanol as solvent and a mass fraction of 3wt%, and heat it at 70℃ for 3h. Take out the surface treated carbon fiber, rinse it with deionized water, put it in an oven and dry it at 70℃ for a day and night to obtain pretreated carbon fiber.

[0044] Step 2: Preparation of heterogeneous structure composite materials: Weigh 6.677g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 2.3191g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and dissolve them in 60mL of deionized water (the molar ratio of nickel nitrate to ferric nitrate is 4:1), stir evenly to prepare a mixed salt solution, and take 0.3g of pretreated carbon fiber and evenly disperse it in the above salt solution (the mass ratio of carbon fiber: nickel iron hydrotalcite = 1:10). Weigh 4.5923g Dissolve sodium hydroxide (NaOH) in 40 ml of deionized water and stir evenly to form a homogeneous alkaline solution. Add the prepared alkaline solution dropwise to the mixed salt solution until the pH value is ≈ 10, and then move the precipitate to a polytetrafluoroethylene reaction vessel and react at 140°C for 14 hours. After the reaction, rinse the excess hydroxide ions in the composite material with deionized water until the composite material appears neutral, and finally dry it to obtain an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material with a mass ratio of 1:10.

[0045] Example 2

[0046] A method for preparing an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material specifically comprises the following steps:

[0047] Step 1: Immerse 1g of tow carbon fiber (CF) in 80mL of acetone, remove glue at 55℃ for 12h, then rinse with deionized water several times, and dry at 80℃ for 24h. Then put the degummed carbon fiber into 80mL of concentrated nitric acid (HNO3), oxidize it at 65℃ for 4h, then rinse it with deionized water until it is neutral, and dry it. Finally, immerse the acidified carbon fiber in 180g of KH550 solution with 4wt% of ethanol as solvent, and heat it at 75℃ for 4h. Take out the surface treated carbon fiber, rinse it with deionized water, put it in an oven and dry it at 80℃ for a day and night to obtain pretreated carbon fiber.

[0048] Step 2: Preparation of heterogeneous structure composite materials: Weigh 2.2257g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 0.773g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) respectively, dissolve in 20mL of deionized water (the molar ratio of nickel nitrate to ferric nitrate is 4:1), stir evenly to prepare a mixed salt solution, and take 0.2g of pretreated carbon fiber and evenly disperse it in the above salt solution (the mass ratio of carbon fiber: nickel iron hydrotalcite = 1:5). Weigh 1.5308g Dissolve 20 ml of sodium hydroxide (NaOH) in 20 ml of deionized water and stir evenly to form a homogeneous alkaline solution. Add the prepared alkaline solution dropwise to the mixed salt solution until the pH value is ≈ 10, and then move the precipitate to a polytetrafluoroethylene reaction vessel and react at 120°C for 18 hours. After the reaction, rinse the excess hydroxide ions in the composite material with deionized water until the composite material appears neutral, and finally dry it to obtain an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material with a mass ratio of 1:5.

[0049] Example 3

[0050] A method for preparing an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material specifically comprises the following steps:

[0051] Step 1: Immerse 0.3g of tow carbon fiber (CF) in 40mL of acetone, remove glue at 50℃ for 9h, then rinse with deionized water several times, and dry at 70℃ for 20h. Then put the degummed carbon fiber into 40mL of concentrated nitric acid (HNO3), oxidize it at 55℃ for 3h, then rinse with deionized water until neutral, and dry it. Finally, immerse the acidified carbon fiber in 80g of KH550 solution with ethanol as solvent and a mass fraction of 3wt%, and heat it at 70℃ for 3h. Take out the surface treated carbon fiber, rinse it with deionized water, put it in an oven and dry it at 70℃ for a day and night to obtain pretreated carbon fiber.

[0052] Step 2: Preparation of heterogeneous structure composite materials: Weigh 6.677g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 2.3191g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and dissolve them in 60mL of deionized water (the molar ratio of nickel nitrate to ferric nitrate is 4:1), stir evenly to prepare a mixed salt solution, and take 0.15g of pretreated carbon fiber and evenly disperse it in the above salt solution (the mass ratio of carbon fiber: nickel iron hydrotalcite = 1:20). Weigh 4.5923 100 g of sodium hydroxide (NaOH) was dissolved in 40 ml of deionized water and stirred to form a homogeneous alkaline solution. The prepared alkaline solution was added dropwise to the mixed salt solution until the pH value was ≈ 11, and then the precipitate was moved to a polytetrafluoroethylene reaction vessel and reacted at 140 ° C for 14 hours. After the reaction, the excess hydroxide ions in the composite material were rinsed with deionized water until the composite material showed neutrality, and finally dried to obtain an industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material with a mass ratio of 1:20.

[0053] Example 4

[0054] A method for preparing an industrial CF / NiCo-LDH heterostructure electromagnetic absorbing material specifically comprises the following steps:

[0055] Step 1: Immerse 0.5g of tow carbon fiber (CF) in 50mL of acetone, remove glue at 50℃ for 10h, then rinse with deionized water several times, and dry at 70℃ for 24h. Then put the degummed carbon fiber into 50mL of concentrated nitric acid (HNO3), oxidize it at 60℃ for 3h, then rinse with deionized water until neutral, and dry it. Finally, immerse the acidified carbon fiber in 100g of KH550 solution with ethanol as solvent and a mass fraction of 3wt%, and heat it at 70℃ for 3h. Take out the surface treated carbon fiber, rinse it with deionized water, put it in an oven and dry it at 70℃ for a day and night to obtain pretreated carbon fiber.

[0056] Step 2: Preparation of heterogeneous structure composite materials: Weigh 6.3027 g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 1.5769 g of cobalt nitrate hexahydrate (Co(NO3)3·9H2O) and dissolve them in 60 mL of deionized water (the molar ratio of nickel nitrate to cobalt nitrate is 4:1), stir evenly to prepare a mixed salt solution, and take 0.3 g of pretreated carbon fiber and evenly disperse it in the above salt solution (the mass ratio of carbon fiber: nickel cobalt hydrotalcite = 1:10). Weigh 4.3346 100 g of sodium hydroxide (NaOH) was dissolved in 40 ml of deionized water and stirred to form a homogeneous alkaline solution. The prepared alkaline solution was added dropwise to the mixed salt solution until the pH value was ≈ 10, and then the precipitate was moved to a polytetrafluoroethylene reaction vessel and reacted at 120 ° C for 12 hours. After the reaction, the excess hydroxide ions in the composite material were rinsed with deionized water until the composite material showed neutrality, and finally dried to obtain an industrial CF / NiCo-LDH heterostructure electromagnetic absorbing material with a mass ratio of 1:10.

[0057] Example 5

[0058] A method for preparing an industrial CF / ZnFe-LDH heterostructure electromagnetic absorbing material specifically comprises the following steps:

[0059] Step 1: Immerse 0.8g of tow carbon fiber (CF) in 70mL of acetone, remove glue at 55°C for 12h, then rinse with deionized water several times, and dry at 75°C for 20h. Then put the degummed carbon fiber into 70mL of concentrated nitric acid (HNO3), oxidize it at 60°C for 4h, then rinse it with deionized water until it is neutral, and dry it. Finally, immerse the acidified carbon fiber in 130g of KH550 solution with ethanol as solvent and a mass fraction of 3wt%, and heat it at 70°C for 4h. Take out the surface-treated carbon fiber, rinse it with deionized water, put it in an oven and dry it at 75°C for a day and night to obtain pretreated carbon fiber.

[0060] Step 2: Preparation of heterogeneous structure composite materials: Weigh 4.3230 g of zinc nitrate hexahydrate ((Zn(NO3)2·6H2O) and 1.4701 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) respectively, dissolve in 40 mL of deionized water (the molar ratio of zinc nitrate to ferric nitrate is 4:1), stir evenly to prepare a mixed salt solution, and take 0.2 g of pretreated carbon fiber and evenly disperse it in the above salt solution (the mass ratio of carbon fiber: zinc iron hydrotalcite = 1:10). Weigh 2.9110 100 g of sodium hydroxide (NaOH) was dissolved in 30 ml of deionized water and stirred to form a homogeneous alkaline solution. The prepared alkaline solution was added dropwise to the mixed salt solution until the pH value was ≈ 11, and then the precipitate was moved to a polytetrafluoroethylene reaction vessel and reacted at 140 ° C for 16 hours. After the reaction, the excess hydroxide ions in the composite material were rinsed with deionized water until the composite material showed neutrality, and finally dried to obtain an industrial CF / ZnFe-LDH heterostructure electromagnetic absorbing material with a mass ratio of 1:10.

[0061] Figure 1 The XRD spectrum of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 is shown in FIG. Figure 1 A broad diffraction peak can be found at 2θ=25.3°, corresponding to the (002) crystal plane of graphite carbon. After the introduction of NiFe-LDH, the peaks at 2θ=11.41° and 2θ=34.43° correspond to the (003) and (012) crystal planes of NiFe-LDH, respectively, proving that NiFe-LDH was successfully grown in situ on the surface of industrial CF.

[0062] Figure 2 and 3 This is a SEM picture of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1. It can be seen from the figure that the industrial carbon fiber is in the form of one-dimensional fibers, randomly overlapped into a three-dimensional conductive network, and nickel-iron hydrotalcite is uniformly attached to the surface of the industrial carbon fiber.

[0063] Figure 4 The electromagnetic parameter diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1 (loading amount is 5wt%). Figure 4 It can be observed that the real part of the complex dielectric constant fluctuates in the range of 5.3 to 11.9, and the imaginary part of the dielectric constant remains at 1.9 to 3.8, indicating that the composite absorber has high dielectric loss performance. The real part of the dielectric constant has a resonance peak in the range of 10 to 16 GHz, which can be considered to be caused by the interface polarization between the different interfaces of the nanosheet layer and the carbon fiber. At the same time, the real part of the magnetic permeability remains at 1.0 to 1.6, which is significantly higher than most similar electromagnetic absorbers. This is mainly due to the strong magnetic properties of NiFe-LDH, and it greatly balances the impedance matching of the composite material.

[0064] Figure 5 This is a reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 1. When the composite material has a doping amount of 5wt% and a thickness of 2.04mm, its effective bandwidth is 7.02GHz (10.98-18GHz), and its maximum absorption effect of -57.77dB is achieved at 12.64GHz. At the same time, within the frequency band of 1-18GHz, the composite material can absorb more than 90% of the electromagnetic waves, accounting for 86% of the total frequency band.

[0065] Figure 6 This is the reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 2. Figure 6 It can be seen that when the thickness is 4.99 mm, the optimal reflection loss is -42.55 dB, and at the matching thickness of 5.47 mm, the maximum effective bandwidth is 2.84 GHz, and its electromagnetic absorption effect is slightly worse than that of Example 1.

[0066] Figure 7 This is the reflection loss diagram of the industrial CF / NiFe-LDH heterostructure electromagnetic absorbing material prepared in Example 3. Figure 7 It can be seen that when CF:LDH=1:20, the microwave absorption effect of the heterogeneous structure composite material is poor, and the minimum reflection loss value at a thickness of 5.96 mm is only -4.5 dB, and its electromagnetic absorption effect is quite different from that of Example 1.

[0067] Figure 8 This is the reflection loss diagram of the industrial CF / NiCo-LDH heterostructure electromagnetic absorbing material prepared in Example 4. Figure 8 It can be seen that when CF:NiCo-LDH=1:10, at a thickness of 1.51 mm, the optimal reflection loss value at a frequency of 17.86 GHz is -47.07 dB, and the maximum effective bandwidth at a matching thickness of 1.81 mm is 5.86 GHz, which indicates that the composite material can absorb 99.99% of the incident electromagnetic waves.

[0068] Fig. 9 This is a single thickness reflection loss diagram of the industrial CF / ZnFe-LDH heterostructure electromagnetic absorbing material prepared in Example 5. Fig. 9 It can be seen that when the mass ratio of carbon fiber to hydrotalcite is 1:10, the maximum absorption bandwidth of the heterostructured CF / ZnFe-LDH composite material at a thickness of 1.48 mm is 3.0 GHz, and it has a minimum reflection loss value of -41.26 dB at a thickness of 6 mm, showing good microwave absorption capability.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material, characterized by: The electromagnetic wave absorbing material consists of industrial carbon fiber and nano-sheet hydrotalcite. The industrial carbon fiber is in one-dimensional fiber shape, and hexagonal nano-sheet hydrotalcite is in-situ grown on the surface of the industrial carbon fiber.

2. A method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 1, characterized in that: The method comprises the following steps: Step 1: preparing pretreated CF: soaking the tow carbon fiber in acetone, concentrated nitric acid, and a silane coupling agent / ethanol mixed solution in turn for surface treatment, and washing and drying after each surface treatment before the next surface treatment, to finally obtain pretreated carbon fiber; Step 2: Prepare a heterostructure composite material: dissolve metal salt 1 and metal salt 2 in deionized water, immerse the pretreated carbon fiber obtained in step 1 in the above salt solution, and after uniform dispersion, use an alkaline solution to adjust the pH value of the above mixed solution, and then carry out a hydrothermal reaction. After sufficient reaction, the reactant obtained is washed and dried to obtain an industrial CF / LDH heterostructure electromagnetic absorbing material.

3. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 1, the mass volume ratio of the tow carbon fiber, acetone, concentrated nitric acid, and silane coupling agent / ethanol is 0.1-30 g: 0.1-100 mL: 0.1-100 mL: 0.1-200 g.

4. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 1, the temperatures and corresponding times of the acetone, concentrated nitric acid, and silane coupling agent / ethanol treatments are 8-12 h / 40-60 ° C, 1-5 h / 50-70 ° C, and 1-5 h / 60-80 ° C, respectively, wherein the mass fraction of the silane coupling agent / ethanol is 1 wt% to 10 wt%, and the silane coupling agents include KH450, KH550, KH560, and KH570.

5. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 1, the drying temperature of the carbon fiber at each stage is 60 to 80° C., and the drying time is 1 to 48 hours.

6. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 2, the molar ratio of the metal salt 1 to the metal salt 2 is 1 to 4:

1.

7. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2 or 6, characterized in that: In step 2, the metal salt 1 is one of nickel salt, magnesium salt, cobalt salt, zinc salt, calcium salt or copper salt; the metal salt 2 is one of iron salt, aluminum salt, chromium salt or manganese salt.

8. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 2, the mass ratio of the carbon fiber to the hydrotalcite is 1:1-30.

9. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In step 2, the alkaline solution is one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, ammonia water, and sodium bicarbonate solution.

10. The method for preparing the industrial carbon fiber / hydrotalcite heterostructure electromagnetic absorbing material according to claim 2, characterized in that: In the step 2, the pH of the CF / LDH precipitate is 9 to 14, the reaction temperature is 50 to 220° C., and the reaction time is 1 to 20 hours.

Citation Information

Patent Citations

  • A method for preparing electromagnetic wave absorbing materials from hydrotalcite-based composite nanofibers

    CN111850821B